Reforma da educação superior e gestão das universidades federais: o planejamento institucional na Universidade Federal de Viçosa - Deus, Maria Alba Pereira de (2008)
This study is focused on the policies of reform of higher education in Brazil as part of the process of structural adjustment and reforms undertaken since the end of the 1980s under the auspices of international agencies of capital and the elite rulers, approaching its effects for the universities from the federal government of Fernando Henrique Cardoso. As part of the neoliberal policies implemented since the Collor de Melo s government, deepened in Cardoso s government and continued in Lula s government, this project is not exclusive of the national bourgeoisies, but the result of the subordination of those bourgeoisies for the bourgeois international project to the periphery of capitalism. It was proposed to investigate whether the plans for the management of Federal Institutions of Higher Education - FIHE contribute, in an administrative sphere, to operate the counter-reform of higher education within them, reflecting an institutional development and a new kind of intellectual, in tune with this project of sociability. Assuming that the goals and academic and administrative priorities expressed in the Institutional Development Plan - IDP, of the FIHE, in the management plans and resolutions corroborate to redefine its institutional profile according to the hegemonic project of restructuring and adjustment of the FIHE to the mercantile and business logic and the decline responsibility of the State to the public university, analyzed the process of construction of the IDP at the Federal University of Viçosa - MG and its management plans for 2001 and 2005. PDI in UFV failed to materialize, because: the seemingly contradictory nature of the government policies had caused insecurity in the administration, about the financing of IDP projects; the lack of articulation and academicpolitical affinities of the involved subjects and the university top management; in addition to immediatism of successive administrations to impose its own strategic plan hampered the construction of the IDP as expression of an institutional policy instrument or academic project of the community. The statements and documents express the choice of entrepreneurist model and acceptance of its leaders and apparently, for many of the academic community, of a reconfiguration process of the public university model and functions, which is manifested in the rapid adhesion of the UFV to the Program to support the Federal University plans of restructuring and expansion REUNI, in 2007. The REUNI has already shown as a coherent and effective instrument of hegemony of the government in building the consensus of FIHE for its quantitative expansion, contracted with temporary and limited supply of resources, even if this leads to intensification and deterioration of quality of production and academic formation, referenced in teaching and research, suggesting that its impact on activities end of the university are monitored and evaluated.